PENDIDIKAN, PERUBAHAN SOSIAL BUDAYA DALAM MEMBANGUN MODERNISASI PEMBANGUNAN BANGSA - Anita (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
Education is essentially a conscious and deliberate effort with full responsibility carried out by adults to children so that interactions arise between the two so that children reach the desired maturity which is carried out gradually and continuously in all complementary environments (households, schools, communities). ). Social is a natural aspect of the individual that has existed since humans were born. Culture and education have a reciprocal relationship because culture can be preserved and developed by passing on culture from generation to generation through education, both formally, non-formally and informally. On the other hand, the form, characteristics, and implementation of education are also determined by the culture of the community where the educational process takes place (Tirtarahardja and Sulo, 2005). If education is neglected, it can be assumed that the socio-culture of a nation will experience extinction because there is no cultural transfer process so that no one preserves and develops culture. Every society in its life must experience changes. By their nature, the changes that occur not only lead to progress, but can also lead to setbacks. The social changes that have occurred have existed since ancient times. There are times when change happens so quickly that it confuses those who deal with it. Social change is a symptom inherent in every society. Changes that occur in society will cause a mismatch between the social elements that exist in society, resulting in a pattern of life that is not in accordance with its function for the community concerned. Modernization is the process of being modern. The term modern comes from the word modo which means the present. Thus, modernization can be interpreted as a way of life that is in accordance with the current situation, or the present context. If the way of life of a society is as inherited by its ancestors or predecessor generations, then the society is called a traditional society. The term tradition comes from the word traditum which means inheritance. The emphasis of the notion of modernization is on technology and social organization.